2023
DOI: 10.1002/fsn3.3833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of gluten‐free diet and Mediterranean diet on autoimmune system in patients with Hashimoto's thyroiditis

Mutlu Tuçe Ülker,
Gözde Arıtıcı Çolak,
Murat Baş
et al.

Abstract: Hashimoto's thyroiditis is an autoimmune disease in which thyroid cells are attacked through cell‐and antibody‐mediated immune processes. A gluten‐free diet reduces antibody concentration and regulates thyroid autoimmunization. Mediterranean diet reduces oxidative stress. This study evaluates the short‐term effects of Mediterranean, gluten‐free, and Mediterranean gluten‐free dietary patterns on thyroid function and autoantibody levels of patients. The 40 patients with Hashimoto's thyroiditis included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Forkhead box transcription factor 3 ( foxp3 ) is essential for the development and function of regulatory T cells (Tregs) and plays a role in acquiring oral tolerance. In children with IgE-mediated CMA, the acquisition of tolerance has been associated with the demethylation of foxp3 's Treg-specific demethylated region (TSDR) [ 31 , 27 ]. Other studies have shown that gluten can impact the microbiome, increase intestinal permeability, and influence oxidative stress, potentially affecting epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box transcription factor 3 ( foxp3 ) is essential for the development and function of regulatory T cells (Tregs) and plays a role in acquiring oral tolerance. In children with IgE-mediated CMA, the acquisition of tolerance has been associated with the demethylation of foxp3 's Treg-specific demethylated region (TSDR) [ 31 , 27 ]. Other studies have shown that gluten can impact the microbiome, increase intestinal permeability, and influence oxidative stress, potentially affecting epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%